Comments on the "Metallic nanoparticles (Cu, Ag, Au) in chalcogenide and oxide glassy matrices..." - Kavetskyy, T.S.; Stepanov, A.L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Comments on the “Metallic nanoparticles (Cu, Ag, Au) in chalcogenide and oxide glassy matrices: comparative assessment in terms of chemical bonding” // Semiconductor Physics, Quantum Electronics & Optoelectronics, 20(1), p. 26-33 (2017).